MULTIDETECTOR COMPUTED TOMOGRAPHY IMAGING FEATURES AND OVERALL SURVIVAL OF PATIENTS WITH HEPATOCELLULAR CARCINOMA TREATED AT K HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical and laboratory characteristics, multi-detector computed tomography (MDCT) features, and overall survival of patients with hepatocellular carcinoma (HCC) treated at K Hospital.Materials and Methods: A cross-sectional descriptive study with longitudinal follow-up was conducted on 307 patients diagnosed with hepatocellular carcinoma at K Hospital from January 2020 to December 2020 (with follow-up until August 2022).Results: The majority of patients were in the 41-60 age group (51.8%), male (88.6%), with a normal performance status (91.9%), and a background of chronic hepatitis B infection (81.4%). Regarding tumor characteristics, the mass-forming type accounted for 99.3%, with 67.1% located in the right lobe; most were solitary tumors (56.7%), and 44.3% had a size ranging from 3-7 cm. On MDCT, 74.6% showed decreased attenuation pre-contrast, and 89.3% exhibited typical post-contrast enhancement. Regarding disease staging, most patients were at the intermediate stage (BCLC B) at 61.6%, followed by BCLC A (17.9%), while only 8 cases were at the terminal stage (BCLC D). The mortality rate was 53.7% (165/307). The highest overall survival was observed in the group with tumor size ≤ 3 cm (mean 28.66 months) and the solitary tumor group (mean 23.21 months). The mean survival time for BCLC stage A was approximately 30 months, stage B was 20 months, while stage D was only 5.6 months (p < 0.05).Conclusion: Although newly diagnosed, most patients with hepatocellular carcinoma were already in the intermediate to advanced stages, resulting in low survival rates.
Keywords: Computed tomography, survival time, hepatocellular carcinoma (HCC).